Prediction and Analysis of Polished Rod Dynamometer Card in Sucker Rod Pumping System with Wear - Dongyu Wang; Hongzhao Liu (Shock and Vibration)
In the oil production process, the wear of friction pairs in sucker rod pumping installations will increase over time, which leads to the failure of the sucker rod pumping system. In order to study the effect of wear on the sucker rod pumping system, a wear model between the plunger and pump barrel was established. By analyzing the wear law, the wear volume and wear time of the pump barrel were calculated under abrasive wear. The forces of the sucker rod microunit were analyzed, and the wave equation of the sucker rod was established. Based on the given boundary and initial conditions, a mixed difference method was used to solve the equation. Taking the no. L2111 well of an oilfield as an example, the change curves of the wear volume and wear time with abrasive particle diameter were plotted, and the polished rod dynamometer card considering wear was predicted. The results showed that the increased clearance caused by wear will reduce the polished rod load on upstroke of the sucker rod pumping system, which could provide a theoretical basis for the next fault diagnosis.